A systematic review of google cardboard used in education - Wang, Zilin; Chan, Moon-Tong (Computers & Education: X Reality, 2024)
Google Cardboard (GC) has emerged as an affordable and user-friendly virtual reality (VR) viewer with significant potential as a pedagogical tool in educational settings. This article presents a systematic review of 35 empirical studies that investigate the application of GC as a VR technology for educational purposes. The review examines various aspects including the teaching subjects, educational levels, mobile applications, operating systems, advantages, and challenges associated with GC implementation, and identifies key areas for future research. The findings highlight that GC offers an accessible and user-friendly VR experience, making it well-suited for most of educational contexts. Its compatibility with both Android and iOS operating systems, along with its ability to motivate learners and facilitate immersive learning experiences, are notable advantages. However, challenges related to display quality, screen refresh rate, cybersickness, and technical issues must be addressed to maximize the effectiveness of GC. Furthermore, the review implicates that providing adequate training and support to users, developing pedagogical frameworks, and exploring subject-specific applications are crucial for successful integration into educational practices. Future research directions involve enhancing user experience, establishing comprehensive guidelines, improving user training and support mechanisms, investigating subject-specific benefits, and evaluating the long-term effects and learning outcomes associated with GC implementation.